Creating and Undoing Legacies of Resilience: Black Women as Martyrs in the Black Community Under Oppressive Social Control - Aniefuna, Leah Iman (Women & criminal justice, 2020)
This paper contextualizes the struggles and contributions of Black motherhood and reproductive justice under police surveillance in Baltimore, Maryland. We conducted semi-structured interviews with mothers regarding their experiences and perceptions of policing in their community during the aftermath of the police-involved death of Freddie Gray. While the literature disproportionately focuses on Black males, little knowledge is known about the struggles and contributions of Black mothers in matters concerning police brutality and the fight against institutional violence. There still remains the question regarding the role of and impact on Black mothers during matters of institutional violence against Black children. We fill this gap by highlighting narratives and lived knowledges within a Black motherhood perspective. Primary themes show that Black women are subject to terror from police and system agents, they face reproductive justice issues, as they are criminalized as mothers—and are affected mentally, but they employ various resistance strategies that strengthen their resilience. Results indicate that Black women are the backbone and martyrs of their communities, but this comes at a tremendous cost because they remain largely unprotected and subject to immeasurable institutional violence and judgment against their mothering strategies.